2020
DOI: 10.3390/app10093320
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between User’s Subjective Feeling and the Degree of Side Curvature in Smartphone

Abstract: To develop a flexible display, smartphones with edge screens with curved displays on both sides of the main screen have been used widely. Considering that small differences in the form of smartphones, such as length, width, and thickness, could affect user experience, the effects of the curvature of the edge screen should be identified. This study aimed to investigate the effects of the curvature of edge screens on subjective feelings of smartphone users and to find out the optimal curvature. In the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…These experiments revealed that 8R is an ideal radius to be used on curved displays and that most users felt most comfortable using the corresponding sample. [5] Edzer Huitema's work focuses on the different applications, along with alternatives and the current status of the world of technology for foldable phones. The paper gives a better understanding of foldable phones, and the different technologies it uses, as well as the different problems solved by it.…”
Section: Literature Surveymentioning
confidence: 99%
“…These experiments revealed that 8R is an ideal radius to be used on curved displays and that most users felt most comfortable using the corresponding sample. [5] Edzer Huitema's work focuses on the different applications, along with alternatives and the current status of the world of technology for foldable phones. The paper gives a better understanding of foldable phones, and the different technologies it uses, as well as the different problems solved by it.…”
Section: Literature Surveymentioning
confidence: 99%
“…Having defined the equation of the circle, we can calculate its derivative for the top and down arcs. Assuming that ϕ| x=0,1 = 0 and ϕ y=0,1 = 0 , one can plot the solution of Equation (5). Without loss of generality, we assume that the azimuthal angle distribution is periodic along the (x; y) plane with the unit period.…”
Section: Model Of Surface-induced Director Alignmentmentioning
confidence: 99%
“…This device represents an electrode-free reflective liquid crystal (LC) optical shutter with photosensitive surface. In fact, flexible substrates have gained a significant attention in recent years, owing to their unprecedented properties, such as light-weight, low cost, small thickness, easy processing and popularity of the devices incorporating flexible components [3][4][5]. Several plastic materials, e.g., polyethylene terephthalate (PET), polycarbonate and polyethersulfone, have been explored as substrates for different applications [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One of these devices is flexible optically rewritable electronic paper (ORW e-paper), which is a reflective display with a photosensitive substrate coated by an azo dye layer with a thickness of 10-15 nm [2][3][4][5][6][7][8][9][10][11]. This display technology has gained significant attention from scholars due to its light weight, low cost, small thickness and easy processing [12][13][14][15]. A shining example of the recent application of liquid crystals with photoalignment technology is the ProMotion display technology, used in iPad Pro displays [16].…”
Section: Introductionmentioning
confidence: 99%